Sponge Cities: Emerging Approaches, Challenges and Opportunities - Dafang Fu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Primarily as a response to increasing flood, impacts, the Chinese Central Government launched a program to implement the Sponge City Concept in selected pilot cities across China in 2013. As a result, the Sponge City Concept is gaining ground and becoming more and more accepted by city governments. The first best practices of the pilot cities are being shared, and international exchange activities between research institutions and cities are providing guidance on the design and implementation of new concepts and technologies. However, there are still many technical, institutional, and socio-economic challenges ahead that hamper wider uptake and up-scaling in China. While the Sponge City Concept is new, the approaches and technologies involved in it, and therefore related challenges and opportunities, have been tried out in many different parts of the globe under the guise of terminologies such as water sensitive cities, Sustainable Drainage Systems, low-impact development, and ABC waters. This book aims to capture a selection of these experiences from China, as well as from other countries in both the developed and developing world, and draws lessons from these experiences relevant to the Sponge City Concept.